Perspectives on contemporary mysticism - Thayer, Nelson S. T. (Journal of religion and health, 1979)
Contemporary mysticism is in continuity with religious mysticism of all ages. Mysticism, like all religion, has an ideological and an experiential dimension. Traditional Freudian theory is inadequate for understanding either the ideological or the cognitive aspect, because it does not adequately account for either the cognitive process or the self-conscious "I." Categories of both ego psychology and the social scientific approach to religion illuminate contemporary mysticism in ways unavailable to the traditional Freudian psychoanalytic approach. The epistemological implications of the mystical attitude are considered, in both the religious and the scientific enterprises.